2017
DOI: 10.1055/s-0037-1603758
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Psychosocial Risk Factors for Stroke

Abstract: Several studies have assessed the link between psychosocial risk factors and stroke; however, the results were inconsistent. We have conducted a systemic review and meta-analysis of cohort or case-control studies to ascertain the association between psychosocial risk factors (psychological, vocational, behavioral, interpersonal, and neuropsychological) and the risk of stroke. Systematic searches were undertaken in MEDLINE, EMBASE, CINAHL, PsycINFO, and the Cochrane Database of Systematic Reviews between 2000 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…6 Similarly, our results are also comparable to associations reported between other psychosocial factors such as work stress, anxiety, and depression and the risk of stroke. [10][11][12][13][14][15] Our findings corroborate studies 1-5 that showed increased risks of acute myocardial infarction, atrial fibrillation, heart failure, and death due to CVD among bereaved parents. To our knowledge, only one study so far has investigated the risk of stroke in parents exposed to the death of a child.…”
Section: Discussionsupporting
confidence: 88%
“…6 Similarly, our results are also comparable to associations reported between other psychosocial factors such as work stress, anxiety, and depression and the risk of stroke. [10][11][12][13][14][15] Our findings corroborate studies 1-5 that showed increased risks of acute myocardial infarction, atrial fibrillation, heart failure, and death due to CVD among bereaved parents. To our knowledge, only one study so far has investigated the risk of stroke in parents exposed to the death of a child.…”
Section: Discussionsupporting
confidence: 88%
“…In a meta-analysis that included 46 studies (30 on psychological factors, 13 on vocational factors, 10 on interpersonal factors, and 2 on behavioral factors), the risk of stroke increased by 39% with psychological factors (HR, 1.39 [95% CI, 1.27–1.51]), 35% with vocational factors (HR, 1.35 [95% CI, 1.20–1.51]), and 16% with interpersonal factors (HR, 1.16 [95% CI, 1.03–1.31]); there was no significant relationship with behavioral factors (HR, 0.94 [95% CI, 0.20–4.31]). 167…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…[1][2][3][4] Previous studies have shown an association between stress and CVD through direct or indirect pathways, [4][5][6][7] and a 1.1-to 1.6-fold increased risk of incident coronary heart disease (CHD) and stroke associated with stress. 8,9 A large retrospective case-control study conducted in 52 countries found that longterm stress was associated with an increased risk of acute myocardial infarction (MI) even after controlling for health behaviors. 6 However, studies in which psychological factors are assessed retrospectively may be more prone to biases.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the association of psychological factors with CVD risk is more controversial compared with other more traditional risk factors (eg, smoking, obesity, diabetes, high blood pressure, elevated cholesterol levels) . Previous studies have shown an association between stress and CVD through direct or indirect pathways, and a 1.1- to 1.6-fold increased risk of incident coronary heart disease (CHD) and stroke associated with stress . A large retrospective case-control study conducted in 52 countries found that long-term stress was associated with an increased risk of acute myocardial infarction (MI) even after controlling for health behaviors .…”
Section: Introductionmentioning
confidence: 99%